A cartografia escolar frente à ciência geográfica renovada: uma questão socioespacial - Rossi, Murilo Vogt (2019)
This work is inserted within a theoretical educational cartographic discussion which main purpose is to analyze the spatial concept as a social condition for teaching maps. For that purpose we adopted the conceptual premises of a renewed geographic science that is the result of an epistemological systematization within Geography. By perceiving that the space concept is not unequivocally presented in this renewed perspective, we searched within the Brazilian School Cartography for the development in the spatial formation of students, focusing essentially in the adopted methodologies an in the spatial geographic development. Concerning the choice of methodology, we elected a predominantly qualitative research approach from a bibliographical analysis of theses that somehow represent a transition or even a development of the spatial approach in the Brazilian School Cartography. From there we identified a noteworthy presence of Jean Piaget’s psychogenetics and of the theory of communication in the teaching and learning processes of an essentially cartesian/Euclidian Cartography, mainly in the basic education. On the other hand, we verified a criticism to this mathematical-logical trend in other studied theses with a conceptual presence marked by a post-Piagetian psychogenetics and new forms of approach to the map teaching from their visual and social-spatial representation, that is, based on a non cartesian/Euclidian trend. Therefore, with this work, we aim for an understanding that leads us to seek a systematization of cartographic knowledge aimed at teachers and researchers, aiming at improvements in the quality of education in the spatial geographical perspective.